Internet of Things for the shopping experience in physical stores - Samuel Efrain Jimenez-Prado; Ricardo Patricio Medina-Chicaiza (Universidad Ciencia y Tecnología, 2023)
This research aims to develop a methodological strategy based on the Internet of Things, which contributes to managing the shopping experience in physical shops. The research's theoretical bases were established by reviewing the literature and applying historical-logical, inductive-deductive, and analysis-synthesis methods. As a result of the study, a strategy consisting of seven phases is proposed: analysis, problem identification, planning, IoT solution, budget, implementation, and evaluation. In addition, it is determined that the Internet of Things allows companies to better understand their customers by collecting data related to their purchasing behavior and designing superior experiences that contribute to the differentiation of the point of sale.